Very Slow Chiral Inversion of Clopidogrel in Rats: A Pharmacokinetic and Mechanistic Investigation - Reist, Marianne; Vos, Marieke Roy-de; Montseny, Jean-Pierre; Mayer, Joachim M.; Carrupt, Pierre-Alain; Berger, Yves; Testa, Bernard (Drug metabolism and disposition, 2000)
Clopidogrel hydrogen sulfate, a thienopyridine derivative, is an ADP receptor antagonist that inhibits platelet aggregation. Clopidogrel is an enantiopure carboxylic ester of S-configuration. The R-enantiomer is devoid of antithrombotic activity and can provoke convulsions at high doses in animals. During preclinical safety evaluation, the possible chiral inversion of clopidogrel has, therefore, been investigated in vivo after repeated oral administration of different dose levels of clopidogrel to male and female rats. Due to rapid metabolism in the liver and low plasma levels of unchanged drug, possible chiral inversion was assessed by monitoring the plasma concentrations of the carboxylic acid metabolites, i.e., the (S)- and (R)-acid, by means of a stereoselective assay. The production of 4 to 8% of (R)-acid was observed. This could be the result of chiral inversion of either clopidogrel or its main metabolite, the (S)-acid. Thus, the possibility of nonenzymatic and enzymatic inversion of clopidogrel and its carboxylic acid metabolite was studied in vitro by chiral HPLC and 1H NMR. Nonenzymatic chiral inversion of clopidogrel at 37°C in 0.1 M phosphate buffers could be observed but was found to be slow, with estimated half-lives of 7 to 12 days, depending on the pH. The (S)-acid was configurationally fully stable up to 45 days in phosphate buffers. Neither clopidogrel nor its carboxylic acid metabolites were subject to enzymatic chiral inversion in isolated rat hepatocyte suspensions. We conclude that the nonenzymatic inversion of clopidogrel accounts for the 4 to 8% of chiral inversion seen in vivo in the rat.